2008
DOI: 10.1103/physrevc.78.031302
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime measurement of candidate chiral doublet bands in theRh103,104isotopes with the recoil-distance Doppler-shift method in inverse kinematics

Abstract: Lifetimes of chiral candidate structures in 103,104 Rh were measured using the recoil distance Doppler-shift method. The Gammasphere detector array was used in conjunction with the Cologne plunger device. Excited states of 103,104 Rh were populated by the 11 B( 96 Zr, 4n) 103 Rh and 11 B( 96 Zr, 3n) 104 Rh fusion-evaporation reactions in inverse kinematics. Three and five lifetimes of levels belonging to the proposed chiral doublet bands are measured in 103 Rh and 104 Rh, respectively. The previously observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Recently, a study of the chiral doublet bands in 103 Rh has shown that the energy separation of these structures depends mainly on the core properties and, to a lesser extent, on the valence quasiparticle coupling [6]. However, the chiral interpretation in the A = 130 region has been questioned due to lifetime measurements [7,8], and it could not be confirmed by lifetime experiments in the nuclei 103 Rh and 104 Rh [9]. In this respect, it is important to understand the necessary conditions leading to the emergence of chiral geometry, one of which is the shape of the corresponding even-even core.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, a study of the chiral doublet bands in 103 Rh has shown that the energy separation of these structures depends mainly on the core properties and, to a lesser extent, on the valence quasiparticle coupling [6]. However, the chiral interpretation in the A = 130 region has been questioned due to lifetime measurements [7,8], and it could not be confirmed by lifetime experiments in the nuclei 103 Rh and 104 Rh [9]. In this respect, it is important to understand the necessary conditions leading to the emergence of chiral geometry, one of which is the shape of the corresponding even-even core.…”
Section: Introductionmentioning
confidence: 98%
“…Based on constrained triaxial covariant density functional theory (CDFT) calculations [2], it has been suggested that multiple chiral doublet (Mχ D) bands can exist in a single nucleus [3][4][5][6][7][8]. To date, the chiral doublet bands, including Mχ D bands, have been reported in more than 40 nuclei in the A ≈ 80 [9,10], 100 [11][12][13][14][15][16][17][18], 130 [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35], and 190 [36][37][38][39][40][41][42] mass regions. For details, see recent reviews [43][44][45][46][47][48][49] or data tables [50].…”
mentioning
confidence: 99%
“…To test the theoretical prediction of chirality in atomic nuclei, significant effort has been devoted to further exploring this interesting phenomenon. Thus far, such chiral doublet bands have been reported in the 80 [2][3][4], 100 [5][6][7][8][9][10][11][12], 130 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and 190 [30][31][32][33][34][35][36] mass regions of the nuclear chart. For details, see recent reviews on nuclear chirality and related topics [37][38][39][40][41][42][43][44][45] or data tables [46].…”
Section: Introductionmentioning
confidence: 99%